Role of Farmers’ Groups in Increasing Robusta Coffee Farmers' Participation in the Village of Linggajati, Sukaratu District, Tasikmalaya Regency - Mela Aruna; Unang; Riantin Hikmahwidi (PT FORMOSA CENDEKIA GLOBAL, 2023)
As one of the most important components of agricultural development, farmer groups must continue to be strengthened in a variety of ways, including by strengthening their roles so that they evolve into strong and independent farmer organizations. Successful agriculture is also characterized by farmer participation in each and every activity. This study aims to determine the level of farmers' participation, the level of farmer group participation, and the link between the levels of farmer group participation and farmer participation. The sampling technique of simple random sampling was used to collect a sample of 42 coffee farmers. Using the Spearman Rank correlation test, the relationship between the significance of farmer groups and farmer participation was examined. The results indicated that the role of the farmer group in all group activities fell within the category of